Mechanism of DNA recognition by the restriction enzyme EcoRV - Zahran, Mai; Daidone, Isabella; Smith, Jeremy C.; Imhof, Petra (Journal of Molecular Biology, 2010)
EcoRV, a restriction enzyme in Escherichia coli, destroys invading foreign DNA by cleaving it at the center step of a GATATC sequence. In the EcoRV-cognate DNA crystallographic complex, a sharp kink of 50° has been found at the center base-pair step (TA). Here, we examine the interplay between the intrinsic propensity of the cognate sequence to kink and the induction by the enzyme by performing all-atom molecular dynamics simulations of EcoRV unbound and interacting with three DNA sequences: the cognate sequence, GATATC (TA); the non-cognate sequence, GAATTC (AT); and with the cognate sequence methylated on the first adenine GACH3TATC (TA-CH3). In the unbound EcoRV, the cleft between the two C-terminal subdomains is found to be open. Binding to AT narrows the cleft and forms a partially bound state. However, the intrinsic bending propensity of AT is insufficient to allow tight binding. In contrast, the cognate TA sequence is easier to bend, allowing specific, high-occupancy hydrogen bonds to form in the complex. The absence of cleavage for this methylated sequence is found to arise from the loss of specific hydrogen bonds between the first adenine of the recognition sequence and Asn185. On the basis of the results, we suggest a three-step recognition mechanism. In the first step, EcoRV, in an open conformation, binds to the DNA at a random sequence and slides along it. In the second step, when the two outer base pairs, GAxxTC, are recognized, the R loops of the protein become more ordered, forming strong hydrogen-bonding interactions, resulting in a partially bound EcoRV-DNA complex. In the third step, the flexibility of the center base pair is probed, and in the case of the full cognate sequence the DNA bends, the complex strengthens and the protein and DNA interact more closely, allowing cleavage. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Direct/indirect readout; EcoRV; Protein-DNA interaction; Sequence recognition